2020
DOI: 10.1007/s11748-020-01364-9
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect of low-dose landiolol on postoperative atrial fibrillation study (PELTA study)

Abstract: Objective To investigate the efficacy of prophylactic administration of low-dose landiolol on postoperative atrial fibrillation (POAF) in patients after cardiovascular surgery. Methods Consecutive 150 patients over 70 years of age who underwent cardiovascular surgery for valvular, ischemic heart, and aortic diseases were enrolled in this single-center prospective randomized control study from 2010 to 2014. They were assigned to three treatment groups: 1γ group (landiolol at 1 μg/kg/min), 2γ group (landiolol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Lanidiolol hydrochloride is a low-dose β-selective blocker that has been shown to give a negative ionotropic effect without the adverse outcomes of β-blockers at a low dose. While debated in literature, The PELTA (Preventive effect of low-dose Lanidiolol on postoperative atrial fibrillation) study showed landiolol has a preventative effect against POAF at low doses in patients who undergo CABG, valvular and aortic surgery [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…Lanidiolol hydrochloride is a low-dose β-selective blocker that has been shown to give a negative ionotropic effect without the adverse outcomes of β-blockers at a low dose. While debated in literature, The PELTA (Preventive effect of low-dose Lanidiolol on postoperative atrial fibrillation) study showed landiolol has a preventative effect against POAF at low doses in patients who undergo CABG, valvular and aortic surgery [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies aimed at determining the capacity of this drug to prevent POAF have involved both patients undergoing cardiac surgery and patients undergoing thoracic surgery; results confirmed landiolol's effectiveness in reducing POAF in the heart surgery setting. However, one study failed to prove any benefit in patients undergoing thoracic surgery [56][57][58]. A recent meta-analysis by Walter et al comparing landiolol to the standard of care (i.e., pooled control group treated with other beta-blockers or diltiazem or no prevention), showed the greater efficacy of the former, which also contributed to a significant reduction in hospital stay costs [59].…”
Section: Short-acting Beta-blockersmentioning
confidence: 99%
“…The final 21 papers were reviewed in full text, and the following were excluded due to the following reasons: 1 study did not have a control group, 6 1 study used sotalol as its study drug, 7 1 study did not segregate outcomes between isolated AF and other forms of SVT, 8 and 1 study focused on the combination therapy of b-blocker and magnesium. 9 Eventually, 17 RCTs, 5,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] fully satisfying our predefined inclusion criteria, were selected from papers published in varying years. Figure 1 The included studies were published between 1983 and 2020 and are from 9 different countries (United States, United Kingdom, Germany, Turkey, Austria, Japan, China, Brazil, Australia) ( Table 1).…”
Section: Literature Retrievalmentioning
confidence: 99%
“…A greater number of studies involved intraoperative (n ¼ 9), 10,13,17,18,20,[22][23][24][25] followed by preoperative (n ¼ 4) [14][15][16]21 and postoperative initiation (n ¼ 4). 5,11,12,19 Starting dose of b-blocker was similarly varied. Among studies with IV administration, dosage ranged from <2 mg/kg/min (n ¼ 1), 5 2 mg/kg/min (n ¼ 4), 5,17,18,24 >2 mg/kg/min (n ¼ 5), 13,19,20,22,25 1 mg (n ¼ 1), 10 and <50 mg/d (n ¼ 1).…”
Section: Jtcvs Open C Volume 3 Number Cmentioning
confidence: 99%
See 1 more Smart Citation